Revitalizing Biology Learning: Innovation and Challenges in the Digital Era - Cartono Cartono (Jurnal Pendidikan Indonesia, 2023)
Along with the development of information technology, biology education needs to experience innovation to maintain its relevance in preparing students to face future demands. This research focuses on innovative strategies that can be applied in biology learning, taking into account the challenges that arise in the digital era. Research methods involve literature analysis, surveys, and case studies to understand the various approaches that have been taken by biology educators. The results of this research show that technology integration, curriculum development that is responsive to the latest scientific developments, and the use of online learning resources are key elements in revitalizing biology learning. Challenges identified include unequal access to technology, teacher training needs, and adapting to rapid changes in learning paradigms. Therefore, this research also explores solutions and strategies to overcome these obstacles. In conclusion, revitalizing biology learning requires a holistic approach that covers various aspects, from technology to innovative teaching strategies. By facing the challenges and taking advantage of the opportunities of the digital era, biology education can become more dynamic and relevant, preparing students to face global changes in the future.